Simulating structural response to water impact - Campbell, J.C.; Vignjevic, R. (International journal of impact engineering, 2012)
Structural response to water impact is important for several areas, including the aerospace and marine industries. Aircraft must be designed to cope with ditching and offshore structures are subject to extreme wave impact and green water loading. The goal is a reliable technique for predicting the structural response to extreme water loading. This is a complex problem involving the interaction of non-linear fluid behaviour (breaking waves, fluid impact) with non-linear structural behaviour (large deformations, contact, material plasticity and damage). This paper gives an overview of the coupled FE/SPH approach for modelling water impact on structures and discusses specific issues related to the analysis of floating structures. The capabilities of the method are illustrated first through comparison with published numerical results for simple problems involving the equilibrium of rigid floats and an initially submerged cylindrical float. Then by comparison with experimental data for the collapse of a metallic helicopter floor structure due to impact with water. Finally the response of a moored buoy to an extreme wave is modelled. The sensitivity of the model to spatial resolution is investigated for the rising cylinder and helicopter floor cases. ► Reliable technique for predicting the structural response to extreme water loading. ► Overview of the coupled FE/SPH approach for modelling water impact on structures. ► Discussion on specific issues related to the analysis of floating structures. ► Capabilities illustrated through the comparison of numerical and experimental results. ► Sensitivity of the model to spatial resolution is investigated.